Congenital malformations caused by Stryphnodendron fissuratum (Leg. Mimosoideae) in guinea pigs (Cavia porcellus). (November 2015) - Macedo, Josenaldo S.; Rocha, Brena P.; Colodel, Edson M.; Freitas, Sílvio H.; Dória, Renata G.S.; Riet-Correa, Franklin; Evêncio-Neto, Joaquim; Mendonça, Fábio S.
Abstract: The aim of this study was to evaluate the toxicity of Stryphnodendron fissuratum pods in guinea pigs ( Cavia porcellus ) and test the hypothesis that this plant has teratogenic effects. Thus, sixteen guinea pigs were randomly divided into four groups of four animals each. Groups 10, 20 and 40 consisted of guinea pigs that received commercial food that contained crushed pods of S. fissuratum at concentrations of 10, 20 and 40 g/kg, respectively, during the period of organogenesis. Control group consisted of guinea pigs under the same management conditions that did not receive crushed pods of S. fissuratum in their food. In all experimental groups, the main clinical signs of poisoning consisted of anorexia, prostration, absence of vocalizations, alopecia, diarrhea, and abortions within the adult guinea pigs. Those that did not abort gave birth to weak, malnourished pups, some of which had fetal malformations. The main teratogenic changes consisted of eventration, arthrogryposis, amelia of the forelimbs, anophthalmia, microphthalmia, anotia and agnathia. The reductions in the number of offspring and the malformations observed in the experimental groups suggest that S. fissuratum affects fetal development and is teratogenic. Highlights: Pods of Stryphnodendron fissuratum cause abortions and congenital malformations. Clinical signs of poisoning consisted of anorexia, alopecia and diarrhea. Main teratogenic changes consisted of eventration and amelia of the forelimbs.